2021
DOI: 10.1016/j.heliyon.2021.e06477
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity, composition, structure and management in agroforestry systems: the case of Kachabira district, Southern Ethiopia

Abstract: Agroforestry is increasingly being identified as an integrated land use enhancing plant diversity while reducing habitat loss and fragmentation. This paper examined species diversity, composition, structure and management in agroforestry systems . Two Kebeles (Kachabira and Mesafe) were purposively selected for this study. Then, farmers who dominantly practiced agroforestry practices such as home garden, parkland and live fence were stratified based on wealth categories. Ten percent of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 14 publications
(13 reference statements)
6
40
0
2
Order By: Relevance
“…Studies conducted in different areas of Ethiopia have found that more than 30% tree species in farm land are exotic tree species (Bajigo and Tadesse, 2015;Endale et al, 2017); indicating the expansion of the exotic tree species into the croplands at the expense of the native trees. However, in contrast, Legesse and Negash, (2021) have found that in Kachabira district of southern Ethiopia; native species comprise a larger portion than introduced species. With species like Catha edulis, Coffea arabica generating cash income (Habte et al, 2021), although a mono-cropping approach is negatively affecting the traditional parkland agroforestry systems (Endale et al, 2017).…”
Section: Constraints On Indigenous Multipurpose Agroforestry Tree Speciesmentioning
confidence: 81%
See 2 more Smart Citations
“…Studies conducted in different areas of Ethiopia have found that more than 30% tree species in farm land are exotic tree species (Bajigo and Tadesse, 2015;Endale et al, 2017); indicating the expansion of the exotic tree species into the croplands at the expense of the native trees. However, in contrast, Legesse and Negash, (2021) have found that in Kachabira district of southern Ethiopia; native species comprise a larger portion than introduced species. With species like Catha edulis, Coffea arabica generating cash income (Habte et al, 2021), although a mono-cropping approach is negatively affecting the traditional parkland agroforestry systems (Endale et al, 2017).…”
Section: Constraints On Indigenous Multipurpose Agroforestry Tree Speciesmentioning
confidence: 81%
“…If people do not have title to land, there is no point in investing in trees which can take a long time for benefits to be realized. Farm household landholding size is also found to be the most important influencing factor that affects the diversity and planting tree species in farm lands ( Legesse and Negash, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Фиксировались как единичные особи, а также группы особей, популяций (в целом или частично) и их сообщества (биологические макросистемы). Первостепенное значение отдавалось полевым исследованиям (изучение в естественной обстановке, непосредственно в природе) (Avdeev, 2020;Cao, 2016;Camarero, 2021;Ding, 2020;Kirby, 2017;Legesse, 2021;Larionov, 2020;Magnus, 2021;Ozherelieva, 2021;Oksuz, 2021).…”
Section: материалы и методы исследованияunclassified
“…55% of forest plantation area [5,6]. This species has wide uses mainly for timber, plywood, fuel wood, poles production, live hedges and carbon sequestration [7][8][9]. These myriad uses has caused a surge in demand for propagation by seed [10].…”
mentioning
confidence: 99%